Decolonizing Muslim Parents' Digital Literacy: A Local Wisdom Approach to Strengthening Family-Based Tarbiyah in the Technological Era - Maidatus Sa'diyah; Siti Rofiáh; Burhanuddin Ridlwan; Ali Saíd; Mohammad Nur Salim; Sholihul Anshori; Wawan Herry Setyawan (Profetika: Jurnal Studi Islam, 2026)
Objective: This research aims to explore the decolonization of digital literacy among Muslim parents through a local wisdom approach to strengthen family-based tarbiyah in the technological era, specifically addressing how Islamic values and pesantren educational principles can enhance parents' capacity for digital discernment while safeguarding children from negative digital influences. Theoretical framework: This study is grounded in Critical Pedagogy by Paulo Freire and the Integration-Interconnection paradigm by Amin Abdullah, combined with the Islamic concept of ta'dib by Syed Muhammad Naquib Al-Attas. Literature review: Current digital literacy frameworks often replicate Western-centric paradigms without integrating local wisdom or Islamic tarbiyah principles. Previous research indicates the critical role of parental digital literacy in children's educational success, yet rarely addresses cultural and religious dimensions specific to Muslim families in Indonesia. The rapid proliferation of digital media presents unique challenges for Muslim families, particularly in preserving Islamic values and fostering ethical digital citizenship within the family unit. Methods: This research employs a descriptive qualitative approach with case study design. While this study primarily employs a qualitative approach, descriptive quantitative data were also collected as supporting evidence through pre- and post-training assessments. This supplementary data was utilized to objectively measure the immediate effectiveness of the training program and to triangulate the qualitative findings Primary data were collected through in-depth interviews with 20 Muslim parents from LKSA Ar-Ridlo Peterongan Jombang who participated in digital literacy training programs, supplemented by observations and documentation analysis using thematic analysis. Results: The findings demonstrate a 70% improvement in parents' digital literacy scores after training (average increase of 33 points). The integration of pesantren educational principles and Islamic local wisdom significantly enhanced parents' capacity to guide children's digital engagement while maintaining tarbiyah values. Key improvements include: 85% of parents became confident in using online learning platforms, 80% able to set parental controls, 90% actively monitor screen time, and 88% regularly discuss digital ethics with children. Implications: This research offers a practical framework for developing culturally sensitive digital literacy programs that align with SDG 4 (Quality Education), SDG 5 (Gender Equality), SDG 10 (Reduced Inequalities), and SDG 16 (Peace, Justice and Strong Institutions). The framework repositions Islamic education as a transformative force in the digital age, with implications extending to philosophical, pedagogical, cultural, and structural dimensions of family-based tarbiyah. Novelty: The novelty lies in the integration of decolonial theory with Islamic tarbiyah principles and Indonesian local wisdom to create a Decolonized Digital Literacy Framework for Muslim Parents (DDLMP), which has not been extensively explored in previous research. This framework provides an alternative to Western-centric digital literacy paradigms by centering Islamic epistemology and Indonesian cultural values.